The Problem of Implementing HOTS Based Learning in Islamic Education at SDN 156 Palembang - Firjilia, Natasya Putri; Andrian, Septi; Fadillah, Zakiyatul; Abdurrahmansyah, Abdurrahmansyah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The findings indicate that the application of HOTS in Islamic Religious Education at SDN 156 Palembang is influenced by the level of preparedness of the school, teachers, students, and parents, as well as various challenges encountered during the learning process HOTS in PAI still encounters several obstacles. Teachers find it difficult to develop lesson plans and evaluation instruments that integrate HOTS principles, students require more time to adapt from memorization-based learning to analytical and evaluative tasks, and parents express varying levels of support, with some struggling to assist their children due to limited understanding of HOTS. Although the school provides adequate facilities, their use has not been maximized in supporting interactive and critical learning activities. The findings highlight that successful HOTS implementation requires comprehensive strategies, including continuous teacher training, optimization of available learning media, and stronger collaboration between schools and parents. This study concludes that HOTS implementation in PAI at SDN 156 Palembang is at an early stage, showing both challenges and opportunities. The study is limited to one school, thus broader generalizations should be approached cautiously. Further research across different school contexts is recommended to enrich understanding and strategies for effective HOTS integration in Islamic education.